Fluorescence Resonant Energy Transfer-Based Quantum Dot Sensor for the Detection of Calcium Ions - Ghosh, Shreya; Chen, Yinghua; George, Anne; Dutta, Mitra; Stroscio, Michael A. (Frontiers in Chemistry, 2020)
A simple optical aptasensor has been synthesized for the detection of calcium ions. This sensing approach employs a semiconductor quantum dot (QD) – gold nanoparticle as the donor – quencher pair and operates on the principle of fluorescence resonant energy transfer (FRET). On binding with calcium ions, the DNA aptamer undergoes a conformational change, which changes the distance between the quantum dot and the gold nanoparticle, conjugated on the 5’ terminal and 3’ terminal of the aptamer respectively. This phenomenon results in the quenching of the quantum dot emission. In this sensor, a maximum quenching of 22.42 ± 0.71 % has been achieved at 35 nM calcium ion concentration while the limit of detection has been determined to be 3.77 pM. The sensor has been found to have high specificity for calcium ions in comparison to other metal ions like sodium, magnesium and potassium. The molecular aptabeacons also demonstrated successful endocytosis and FRET based calcium ion detection in osteocyte cells when conjugated with a cell penetrating peptide (DSS).